Bibliometric and Visualized Analysis of Scientific Publications on Geotechnics Fields - Isah Bela Mulyawati; Doni Fajar Ramadhan (ASEAN Journal of Science and Engineering Education, 2021)
The advancement of civil engineering plays a major role in determining the nation's development. Generally, geotechnical engineering has a great influence as there is a building on the ground. The facts show that there are still many geotechnical problems that arise during the development process. One of the supporting factors in dealing with these problems is the development of research in the geotechnical sector in various fields. This research aims to determine the development of research related to Geotechnical Engineering through a bibliometric distribution map using the VOSviewer application. Data collection is gathered from the dimension site. The keyword used in this study is "geotechnical engineering" with the publication year of the 2017-2020 articles. This search was conducted on 23 October 2020 which resulted in 79,185 articles. The results show that the most productive writer in geotechnical research is Ronald Kerry Rowe. Moreover, China is the largest country in the field of geotechnical research so that many other countries have established cooperative relations with China. The journal that publishes the most articles on geotechnical engineering is the International Journal of Rock Mechanics and Mining Science. As for keyword analysis, it produces bibliometric maps including network visualizations, overlay visualizations, and density visualizations. Four keywords often appear, namely "Displacement", "Strength", "Stress", and "Earthquake". Through the bibliometric approach, researchers can identify keywords on each topic or research that has been done before, it is, therefore, valuable in determining the novelty of the research that will be conducted in the future.